Failure of anti-TNF therapy to reactivate previously septic prosthetic joints. (8th July 2013) - Manolios, Nicholas; Burneikis, Anthony; Spencer, David; Howe, Graydon
Abstract : A patient with long-standing rheumatoid arthritis was admitted with Streptococcus pneumoniae septicaemia and bilateral septic knee joints. He was treated conservatively with intravenous antibiotics and arthroscopic washouts and discharged home on oral antibiotics. Six months posthospital discharge, following re-exacerbation of arthritis, an informed consent was given by the patient to continue antitumour necrosis factor therapy. After 5 years of observation, there has been no recurrence of sepsis and the rheumatoid arthritis remains in remission.